2022
DOI: 10.3390/nu14132776
|View full text |Cite
|
Sign up to set email alerts
|

Non-Responsive and Refractory Coeliac Disease: Experience from the NHS England National Centre

Abstract: We characterised the aetiology of non-responsive coeliac disease (NRCD) and provided contemporary mortality data in refractory coeliac disease (RCD) from our centre. We also measured urine gluten immunogenic peptides (GIPs) in patients with established RCD1 to evaluate gluten exposure in these individuals. Methods: This was a longitudinal cohort study conducted in Sheffield, UK. Between 1998 and 2019, we evaluated 285 adult (≥16 years) patients with NRCD or RCD. Patients with established RCD1 and persisting mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 35 publications
1
17
1
Order By: Relevance
“…This finding is comparable to a study whereby patients with and without histological remission had similar dietitian dietary adherence scores ( n = 44) 16 . This is also clinically useful to know, as it has previously been demonstrated, that the most common cause of persistent symptoms in CD is ongoing gluten exposure 24–27 . Thus, using a specialist dietitian assessment to help identify inadvertent gluten ingestion before considering a more invasive and costly endoscopy with repeat duodenal biopsies is likely to be safe and useful for many patients.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This finding is comparable to a study whereby patients with and without histological remission had similar dietitian dietary adherence scores ( n = 44) 16 . This is also clinically useful to know, as it has previously been demonstrated, that the most common cause of persistent symptoms in CD is ongoing gluten exposure 24–27 . Thus, using a specialist dietitian assessment to help identify inadvertent gluten ingestion before considering a more invasive and costly endoscopy with repeat duodenal biopsies is likely to be safe and useful for many patients.…”
Section: Discussionsupporting
confidence: 82%
“…16 This is also clinically useful to know, as it has previously been demonstrated, that the most common cause of persistent symptoms in CD is ongoing gluten exposure. [24][25][26][27] Thus, using a specialist dietitian assessment to help identify inadvertent gluten ingestion before considering a more invasive and costly endoscopy with repeat duodenal biopsies is likely to be safe and useful for many patients. Despite this, the current recommendation for exploring persistent CD symptoms is that a dietitian assessment be offered after repeat duodenal biopsies have been performed.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the prevalence of complications in the present study was higher than previously reported, although comparisons are difficult to make due to differences in clinical and demographic aspects, and duration of follow-up 30 34. It should be noted that roughly half of the complications in our cohort were due to refractory CD type 1, which is characterised by the best prognosis among the complications of CD, and for which it has recently been suggested that hidden gluten exposure may play a role 18 35. Unfortunately, in this regard, we cannot provide data on measurement of minimal traces of gluten given the retrospective nature of our study.…”
Section: Discussioncontrasting
confidence: 67%
“…Identification of potential clinical targets in the follow-up of patients with CD is a crucial requirement for clinicians. Based on our results, this includes implementing strategies for obtaining and maintaining over time strict adherence to a GFD,9 control of persistent symptoms despite a GFD11 35 40 and obtaining deep mucosal healing. A substantial degree of overlap between these aspects is likely to exist.…”
Section: Discussionmentioning
confidence: 99%
“…The immune response is amplified by capture and presentation of the deamidated peptides by intestinal plasma cells making autoantibodies to tissue transglutaminase 2 (TG2) ( 2 ) and by clonal expansion of CD8 T cells adopting an NK-like cytolytic phenotype ( 58 ). Treatment with a strict, lifelong gluten-free diet generally induces symptom resolution, normalisation of CD serology and healing of the enteropathy but up to 30% of patients experience non-responsive CD ( 9, 10 ).…”
Section: Main Textmentioning
confidence: 99%